The Effect of Promotion, Price, and Location on The Purchase Decision of Dry Cakes - Suci, Wahyu; Eka, Yuni; Suryanikahsari, Rizky (Prosiding Seminar, 2023)
This article aims to determine the effect of promotion, price, and location on purchasing decisions for pastries in Setia Rasa Kec.Pace, Nganjuk Regency. The variables of this study are Promotion (X1), Price (X2), Location (X3), and Purchase Decision (Y). The research location is in the Setia Rasa home industry, Pace District, Nganjuk Regency. They used data collection techniques through interviews, observation, and questionnaires. Based on the tests carried out with multiple linear regression analysis, the t-test shows that Promotion (X1), Price (X2), and Location (X3) have a significant influence on Purchasing Decisions (Y). It is shown from the significant value for the X1 0.000 < 0.05, the X2 0.17 < 0.05, and the X3 0.49 < 005. The F test shows that the variable of Promotion (X1), Price (X2), and Location (X3) simultaneously on Purchasing Decisions at Setia Rasa Home Industry, Pace District, Nganjuk Regency. The correlation test shows that the R-value is 0.869, meaning that the variable of Promotion (X1), Price (X2), Location (X3), and Purchase Decision (Y) have a strong relationship. The variable that has the most dominant influence on purchasing decisions is the promotion variable